El derecho de alimentos: La situación financiera del alimentante y las pensiones alimenticias agregadas - Recalde Gaibor, Jardel Aldahir (2025)
The present study was conducted to analyze how the precarious economic conditions of child support providers, influenced by labor informality and poverty in urban Guayaquil, affect the effectiveness of court-assigned child support payments in Ecuador. The research employed a mixed-methods and descriptive approach, including a survey of 100 parents responsible for child support payments and interviews with family law attorneys. The main findings indicate that 35% of respondents have formal employment, while 30% work in the informal sector. Additionally, 30% earn between $500 and $999 per month. Furthermore, 40% believe greater oversight of how child support payments are used is necessary, and 35% feel that these payments impact other essential expenses. This study reveals that job stability and income levels influence compliance with child support obligations. It also highlights the need for reforms to adjust payment amounts and improve oversight of their use.